2013
DOI: 10.1155/2013/841514
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glutamine Is Superior Than Oral Glucose to Promote Glycemia Recovery in Mice Submitted to Insulin-Induced Hypoglycemia

Abstract: The effect of the oral administration of blood glucose precursors on glycemia recovery and liver glucose production in fasted mice subjected to insulin-induced hypoglycemia (IIH) was investigated. IIH was obtained with increasing doses (from 0.5 to 2.0 U·kg−1) of intraperitoneal regular insulin where glycemia was evaluated from 0 to 300 min after insulin injection. The dose of 1.0 U·kg−1 showed the best results, that is, a clear glycemia recovery phase without convulsions or deaths. Thus, this dose was used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
1
5
0
1
Order By: Relevance
“…This similar fact has also been found in patients and rodents with type 2 diabetes and T1D (Bataglini et al, 2017;Chakera et al, 2018). The blood glucose of fasted normoglycemic mice also drops sharply 60 min after IIH but it recovers almost completely after 300 min (Nunes Santiago et al, 2013). In the present study, only a relatively poor response to hypoglycemia was observed in T1D mice receiving cortisol.…”
Section: The Glycemic Response To Iih After Gdip and Insulin Degludec...supporting
confidence: 90%
See 2 more Smart Citations
“…This similar fact has also been found in patients and rodents with type 2 diabetes and T1D (Bataglini et al, 2017;Chakera et al, 2018). The blood glucose of fasted normoglycemic mice also drops sharply 60 min after IIH but it recovers almost completely after 300 min (Nunes Santiago et al, 2013). In the present study, only a relatively poor response to hypoglycemia was observed in T1D mice receiving cortisol.…”
Section: The Glycemic Response To Iih After Gdip and Insulin Degludec...supporting
confidence: 90%
“…After 30-day treatment, 15 h fasted control and T1D mice received regular insulin to induce IIH and cortisol 15 min later. One hour after IIH, the non-recirculating liver perfusion was performed as previously described (Broetto-Biazon et al, 2009;Nunes Santiago et al, 2013). After an initial period of 10 min of perfusion to stabilize the preparation, samples of the effluent perfusion fluid were collected at five-minute intervals and analyzed for their content of glucose, lactate, pyruvate, ammonia and urea (Bergmeyer, 1974).…”
Section: Liver Perfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…nesse sentido, é interessante observar que no fígado, um órgão essencial para a reutilização de lactato sanguíneo como fonte de energia (por meio da gliconeogênese), a produção de glicose a partir de lactato aumenta rapidamente para concentrações de lactato entre 0,5 e 4 mM, mas tende a se estabilizar entre 4 e 16 mM (SAnTIAGO et al, 2013). Sendo assim, a capacidade gliconeogênica hepática, a partir de lactato, poderia ter papel importante no estabelecimento do LAn e na sua alteração com o treinamento.…”
Section: Considerações Finaisunclassified
“…In this regard, the effects of glucose have previously been compared with those of glutamine, alanine, lactate, and pyruvate (Galende et al, 2009;Hartman et al, 2010;Nunes Santiago et al, 2013;Rodrigues et al, 2011).…”
Section: Introductionmentioning
confidence: 99%